Psychological flexibility mediate the effect of early maladaptive schemas on Psychopathology - Borjali, Ahmad; Bahramizadeh, Hamid; Eskandai, Hossein; Farrokhi, NoorAli (International Journal of Applied Behavioral Sciences, 2018)
Introduction: The present research aims to study the mediation role of psychological inflexibility on the relationship between the schemas domains) and anxiety symptoms. Methods: In order to achieve the study objectives, a sample of 230 students has been selected, applying availability sampling. The applying tools included the short-form of Young questionnaire (YSQ-SF), the acceptance and action questionnaire-II (AAQ-II) and Beck Anxiety Inventory (BAI). Results: Correlation analysis has shown that there is a relationship between the early maladaptive schemas and anxiety symptoms. Furthermore, the path analysis shows a mediation role of psychological inflexibility between disconnection/rejection (2.37, p<0.01) impaired autonomy and performance (3.19, p<0.01), overvigilance/inhibition (2.90, p<0.01) and the anxiety symptoms. Conclusion: The most obvious finding to emerge from this study was that considering some techniques for decreasing psychological inflexibility enhances the outcome of schema therapy. This research managed to answer how the early maladaptive schemas have their effects on the anxiety symptoms in a students’ sample. Further work needs to be done to study the relationship between the early maladaptive schemas and psychological inflexibility in the clinical samples. Declaration of Interest: None.